ANTHROPIC PRINCIPLE OF WORLDVIEW STRUCTURE - Олег ПОГОРЄЛОВ; Мирослава КАРПЕНКО (Епістемологічні дослідження у філософії, соціальних і політичних науках)
Three basic elements of worldview are revealed – «I», Nature, Absolute, which form the sphere of human spiritual culture. Man is physically a part of nature, but through consciousness he is internally separated from it. Man is internally separated from nature through the act of self-identification of consciousness in himself. This is not a cognitive but a being act, by which the «I» as the selfhood of man is unconditionally assumed. Self-identified consciousness is constantly correlated with Nature as a whole as a spiritual entity, in which capacity it exists as a structural element of the worldview. Man is internally separated from the Nature, not by his thought or imagination, but by his self-consciousness, i. e. by the spiritual being, distinct from the material being of the Nature. The «I» has its basis not in man’s biological constitution, i. e., not in the external but in the internal. This basis is the Absolute, with which the «I» is spontaneously related, and outside of which it cannot exist. The Absolute is the reality which exhausts all being and, as such, possesses the ultimate fullness of being, it is eternally primordial, and in relation to all that exists apart from it, it acts as the universal generating beginning. The Absolute is characterized as absolutely unconditional, is the spiritual source of all that exists – the world as a whole. The other two basic elements - Nature and man are two types of spiritual-material integrity – the spiritual component of both is a reflection of the Absolute that created them. The actual expression of the spontaneous correlation of the «I» with the Absolute is spiritual creativity, which is expressed in the production of mythological, religious-symbolic and speculative ideas about the Absolute and in the construction on this basis, respectively, mythological, religious and philosophical pictures of the world.